1987
DOI: 10.1148/radiology.163.2.3562827
|View full text |Cite
|
Sign up to set email alerts
|

Occult breast cancer: prevalence and radiographic detectability.

Abstract: The radiographic detectability of occult breast cancer has been difficult to determine. A prospective study of breast disease was carried out that involved the performance of subcutaneous mastectomies in 519 consecutive cases of traumatic or initially unexplained death in New Mexico. Routine mammograms and radiographs of 1-cm specimens were obtained. At least 18 biopsies were performed in each subject. Carcinoma was identified in ten subjects; one subject had metastatic carcinoma from the lung, and two subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…However, the smallest breast cancer in this study, which was 7 mm in diameter and located in the superficial outer quadrant, was detected on early 99m Tc-MIBI scintimammography as an area of focal accumulation. In women with dense breasts, mammography has a false-negative rate of 25%-45% [40]. In the present study, all four patients with indeterminate findings on mammography because of dense breast tissue showed abnormal accumulation on scintimammography using 99m Tc-MIBI and 99m Tc-HMDP.…”
Section: Discussionsupporting
confidence: 41%
“…However, the smallest breast cancer in this study, which was 7 mm in diameter and located in the superficial outer quadrant, was detected on early 99m Tc-MIBI scintimammography as an area of focal accumulation. In women with dense breasts, mammography has a false-negative rate of 25%-45% [40]. In the present study, all four patients with indeterminate findings on mammography because of dense breast tissue showed abnormal accumulation on scintimammography using 99m Tc-MIBI and 99m Tc-HMDP.…”
Section: Discussionsupporting
confidence: 41%
“…13,14 A few other autopsy studies have found undetected DCIS and invasive carcinomas in the breast tissues of women who died accidentally. [15][16][17][18] Certainly, among older women who were diagnosed incidentally with breast carcinoma at autopsy (the disease never altered their lives), it may be argued that, because they died of other diseases, the detection of these innocuous tumors when the individual was alive would have led only to "harms" through unnecessary psychological trauma and totally unnecessary treatment. The autopsy studies that have evaluated women who died accidentally, however, represent a very different group.…”
Section: Ductal Carcinoma In Situmentioning
confidence: 99%
“…Many studies have demonstrated that x-ray mammography is the most effective tool and is superior to phyical examination alone for the early detection of breast cancer. [2,3] Mammography has a relatively high sensitivity in the range of 85% -90%, especially in the examination of fatty breasts. Unfortunately, mammography is limited and less reliable in detecting breast cancer in women with dense breasts.…”
Section: Discussionmentioning
confidence: 99%